Case Report: Advanced grade 2 meningioma with PBRM1 inactivation with prolonged response to immunotherapy - Reusch, Ellen; Peh, Keng Hee; Morgan, Rachael; Momo, Harry; Orren, David; Rock, Stephanie; Pittman, Thomas; Neltner, Janna; Kolesar, Jill; Villano, John (Frontiers in Oncology, 2025)
Meningiomas are the most common primary tumor in the central nervous system, yet an effective systemic treatment remains a challenge. We present a grade 2 meningioma that resulted in a positive and prolonged response to pembrolizumab. Our case had polybromo-1 (PBRM1) and BAP1 functional loss, tumor mutational burden of 4 Muts/Mb, stable microsatellite status, and a PD-L1 tumor proportion score of <1%. We add to the limited literature regarding PBRM1 mutations in meningiomas. We discuss our findings in relation to the ongoing investigation of immune checkpoint inhibitor therapy in treating higher-grade refractory meningiomas.